The robust demands of the good : ethics with attachment, virtue, and respect - Pettit, Philip, 1945- (Uehiro series in practical ethics., 2015)
Philip Pettit offers a new insight into moral psychology. He shows that attachments such as love, and certain virtues such as honesty, require their characteristic behaviours not only as things actually are, but also in cases where things are different from how they actually are. He explores the implications of this idea for key moral issues.